Variation in Phytochemical Composition Reveals Distinct Divergence of (L.) Burm.f. From Other Species: Rationale Behind Selective Preference of in Nutritional and Therapeutic Use - Priyankar Dey PhD; Somit Dutta MSc; Anurag Chowdhury MSc; Abhaya Prasad Das PhD; Tapas Kumar Chaudhuri PhD (SAGE Publishing, 2017)
In the present study, we have phytochemically characterized 5 different abundant Aloe species, including Aloe vera (L.) Burm.f., using silylation followed by Gas Chromatography-Mass Spectrometry technique and compared the data using multivariate statistical analysis. The results demonstrated clear distinction of the overall phytochemical profile of A vera , highlighted by its divergent spatial arrangement in the component plot. Lowest correlation of the phytochemical profiles were found between A vera and A aristata Haw. (−0.626), whereas highest correlation resided between A aristata and A aspera Haw. (0.899). Among the individual phytochemicals, palmitic acid was identified in highest abundance cumulatively, and carboxylic acids were the most predominant phytochemical species in all the Aloe species. Compared to A vera , linear correlation analysis revealed highest and lowest correlation with A aspera ( R 2 = 0.9162) and A aristata ( R 2 = 0.6745), respectively. Therefore, A vera demonstrated distinct spatial allocation, reflecting its greater phytochemical variability.